(untitled) (Revista Electrónica REDINE, 2020)
This article intends to expose the different points of view on the nature of mathematical objects as entities in the ontological and as theories developed in the philosophy of mathematics from the point of view of Platonism arising in its source idea and in counterpart of the anti -platonism as an alternate theory that refutes it. The ontological confrontation of mathematics focused between Platonism and structuralism, the two main currents of the philosophy of mathematics that are debated about the presence and nature of mathematical objects, is addressed